RADEC LEARNING DESIGN MODELTO TRAIN THE 21st CENTURY SKILLS IN ELEMENTARY SCHOOL - Nanang Rosid Abidin; Eko Andy Purnomo; Venissa Dian Mawarsari (Universitas Muhammadiyah Semarang, 2021)
Changes in the orientation of 21st-century education by training soft skills are of particular concern to the world of education. Revise the 2013 curriculum by adding skills (1). Critical Thinking and Problem-Solving; (2) Creativity and Innovation; (3) Communications; (4) Collaboration that is included in each learning content gives a message about the importance of this skill. This was done because Indonesia's low position in the PISA ranking based on the Education Development Index released in 2016 was ranked 61, 62, and 63 out of 72 countries for the fields of science, reading, and mathematics. Facts on the ground, teachers are still not well prepared for learning. Conventional teaching methods with lectures and teacher-centered are still the favorites. Answering these challenges, lesson design using a learning model (Read, Answer, Discuss, Explain, Create) RADEC can be used as an alternative solution to train 21st-century skills in elementary schools. The research model used is descriptive qualitative from the results of observations, documentation, and interviews. The results showed that students were trained to analyze critical thinking, creativity, and innovation, to communicate and collaborate well at the stages of the RADEC learning model. Students are more active and interested in learning, it is easier to understand the material and get satisfactory results.Keywords: RADEC, 4C, lesson design